Implementation of public sector marketing in Indonesia: Internet-based study official provincial government website - Supriadi, Hary; Imbaruddin, Amir (Universitas Wiralodra, 2023)
The quality of performance and public services in Indonesia still requires significant improvement. One approach that can be used to improve this quality is the application of marketing concepts. This research aims to identify the practice of implementing a marketing approach, especially the 4P1C strategy (product, price, place, promotion, and customer focus and relations) in the public sector in Indonesia. The method used is content analysis, where marketing strategy practices are detected through narratives on the official pages of provincial government agencies in Indonesia. 4,678 pages of text (1,126,018 words) were copied from 34 official Provincial Government websites for analysis. Analysis was carried out on manifest content using an a priori coding approach and hidden content supported by the QDA Miner application. The analysis results show that provincial governments in Indonesia still need to maximize the implementation of the 4P1C marketing strategy fully. The element of